Inhibiting 5‐lipoxygenase prevents skeletal muscle atrophy by targeting organogenesis signalling and insulin‐like growth factor‐1. Issue 6 (11th October 2022) - Kim, Hyun‐Jun; Kim, Seon‐Wook; Lee, Sang‐Hoon; Jung, Da‐Woon; Williams, Darren R.
Abstract: Background: Skeletal muscle atrophy can occur in response to numerous factors, such as ageing and certain medications, and produces a major socio‐economic burden. At present, there are no approved drugs for treating skeletal muscle atrophy. Arachidonate 5‐lipoxygenase (Alox5) is a drug target for a number of diseases. However, pharmacological targeting of Alox5, and its role in skeletal muscle atrophy, is unclear. Methods: The potential effects of gene knockdown and pharmacological targeting of Alox5 on skeletal muscle atrophy were investigated using cell‐based models, animal models and human skeletal muscle primary cells. Malotilate, a clinically safe drug developed for enhancing liver regeneration and Alox5 inhibitor, was investigated as a repurposing candidate. Mechanism(s) of action in skeletal muscle atrophy was assessed by measuring the expression level or activation status of key regulatory pathways and validated using gene knockdown and RNA sequencing. Results: Myotubes treated with the atrophy‐inducing glucocorticoid, dexamethasone, were protected from catabolic responses by treatment with malotilate (+41.29%, P  < 0.01). Similar anti‐atrophy effects were achieved by gene knockdown of Alox5 (+30.4%, P  < 0.05). Malotilate produced anti‐atrophy effects without affecting the myogenic differentiation programme. In an in vivo model of skeletal muscle atrophy, malotilate treatment preserved muscle force/strength (grip strength: +35.72%, latency to fall: +553.1%, P  < 0.05), increased mass and fibre cross‐sectional area (quadriceps: +23.72%, soleus: +33.3%, P  < 0.01) and down‐regulated atrogene expression (Atrogin‐1: −61.58%, Murf‐1: ‐66.06%, P  < 0.01). Similar, beneficial effects of malotilate treatment were observed in an ageing muscle model, which also showed the preservation of fast‐twitch fibres (Type 2a: +56.48%, Type 2b: +37.32%, P  < 0.01). Leukotriene B4, a product of Alox5 activity with inflammatory and catabolic functions, was found to be elevated in skeletal muscle undergoing atrophy (quadriceps: +224.4%, P  < 0.001). Cellular transcriptome analysis showed that targeting Alox5 up‐regulated biological processes regulating organogenesis and increased the expression of insulin‐like growth factor‐1, a key anti‐atrophy hormone (+226.5%, P  < 0.05). Interestingly, these effects were restricted to the atrophy condition and not observed in normal skeletal muscle cultures with Alox5 inhibition. Human myotubes were also protected from atrophy by pharmacological targeting of Alox5 (+23.68%, P  < 0.05). Conclusions: These results shed new light on novel drug targets and mechanisms underpinning skeletal muscle atrophy. Alox5 is a regulator and drug target for muscle atrophy, and malotilate is an attractive compound for repurposing studies to treat this disease.